Kewarisan Istimewa Gharawain Pasal 178 Ayat (2) Kompilasi Hukum Islam Dalam Isu Kesetaraan Perspektif Feminis Legal Teori - Ahmad Faza Bin Naja (Nurul Qarnain College of Sharia Studies, Jember, 2023)
Article 173 of the Compilation of Islamic Law is an article regarding inheritance. This article contains the issue of